ACE inhibitor-induced small bowel angioedema, mimicking an acute abdomen - Parreira, Rafaela (J Surg Case Rep, 2020)
Angiotensin-converting enzyme (ACE) inhibitors are the leading cause of drug-induced angioedema, being the face, tongue, lips and upper airway the most affected ones. We describe a case of a 32-year-old white female with angioedema of small intestine after 1 month of perindopril therapy. The patient presented severe abdominal pain, nausea and vomiting. Laboratory analyses revealed mild leukocytosis and abdominal computed tomography (CT) showed unspecific findings, including segmental jejunal wall thickening without obstruction and ascites. Regarding the clinical findings, similar to an acute abdomen with no clear cause, the patient underwent an emergency laparoscopy that excluded other pathological features. The symptoms recurred 1 month after and the CT scan revealed the same pattern. Perindopril was stopped and the patient improved, concluding that ACE inhibitor-induced visceral angioedema was responsible for this clinical presentation.